2013
DOI: 10.1002/gbc.20022
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in concentration, composition, age, and fluxes of particulate organic carbon exchanged between the floodplain and Amazon River

Abstract: [1] The composition, sources, and age of particulate organic matter were determined in an Amazonian river-floodplain system during rising, high, falling, and low water periods over 7 yr (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), and a mass balance for total organic carbon (dissolved and particulate) was estimated. The Curuai floodplain, composed of several temporally interconnected lakes, is permanently connected to the Amazon River via channels. Organic matter (OM) is imported to the floodplain from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
3
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 60 publications
(99 reference statements)
10
107
3
2
Order By: Relevance
“…plants (Moreira-Turcq et al, 2013). By contrast, the data imply that main stem POC in April, during rising waters, is influenced by a greater proportion of POC from the upstream tributaries, including POC transported by the Solimões and Madiera Rivers to the main stem, which are more 13 C-enriched and N-enriched (Table 3; Fig.…”
Section: Radiocarbon Distribution Of Poc Flux At óBidosmentioning
confidence: 80%
See 2 more Smart Citations
“…plants (Moreira-Turcq et al, 2013). By contrast, the data imply that main stem POC in April, during rising waters, is influenced by a greater proportion of POC from the upstream tributaries, including POC transported by the Solimões and Madiera Rivers to the main stem, which are more 13 C-enriched and N-enriched (Table 3; Fig.…”
Section: Radiocarbon Distribution Of Poc Flux At óBidosmentioning
confidence: 80%
“…Particle transport studies have reported significant geographical and temporal variations in the fraction of marine and terrestrial primary productivity exported (export efficiency) and sequestered (transfer efficiency) in the deep ocean (Hedges and Oades, 1997;Moreira-Turcq et al, 2013). The following chapters of this dissertation aim to expand mechanistic understanding of this variation in POC export and transfer efficiency by (1) comparing multiple factors that govern the fraction of primary productivity transferred to the deep ocean and (2) assessing different empirical approaches to sampling and analyzing the dynamics of POC exported from the water column and through rivers.…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The periodic floods intensify the exchange of organic compounds, nutrients and minerals between rivers, lakes and flooded soils (Junk, 1997). Although only 10-20 % of the organic matter (OM) produced in the water column reaches the sediment and is finally buried (Devol et al, 1984), the sediments in these lakes are important sinks of carbon (Moreira-Turcq et al, 2004). Most of the sedimentary organic matter (SOM) in freshwater systems is derived from terrestrial vascular plants (Goñi and Hedges, 1992;Moreira-Turcq et al, 2004;Mortillaro et al, 2011).…”
Section: R L Sobrinho Et Al: Spatial and Seasonal Contrasts Of Sedmentioning
confidence: 99%
“…Although only 10-20 % of the organic matter (OM) produced in the water column reaches the sediment and is finally buried (Devol et al, 1984), the sediments in these lakes are important sinks of carbon (Moreira-Turcq et al, 2004). Most of the sedimentary organic matter (SOM) in freshwater systems is derived from terrestrial vascular plants (Goñi and Hedges, 1992;Moreira-Turcq et al, 2004;Mortillaro et al, 2011). In the Amazon basin, many studies have characterized the suspended particulate organic matter (SPOM) in the rivers and the floodplain lakes and concluded that the main sources of OM to the aquatic system are the forests and the upstream Andean soils (e.g., Hedges et al, 1986Hedges et al, , 1994Quay et al, 1992;Victoria et al, 1992;Moreira-Turcq et al, 2004Aufdenkampe et al, 2007;Mortillaro et al, 2011;Zell et al, 2013b).…”
Section: R L Sobrinho Et Al: Spatial and Seasonal Contrasts Of Sedmentioning
confidence: 99%